Բարսեղ Կեսարացու և Գրիգոր Նարեկացու ճառերի համեմատական վերլուծություն - Վ. Ս. Կարապետյան (ՀՀ ԳԱԱ հրատ.)
Речи Григора Нарекаци и Барсега Кесараци, озаглавленные “Смотри на себя”,–это богословские труды, написанные в форме нравственной проповеди. Основой для них послужили заповеди пророка Моисея /Второй закон, Д. 9-10/, призывавшего еврейский народ к самоочищению и нравственному совершенствованию во имя спасения человечества. The speeches by Grigor Narekatsi and Barsegh Kesaratsi entitled "Look at yourself," are theological works, written in the format of moral sermon. They were based on the commandments of the Prophet Moses / Second Law, D. 9-10 / who called the Jewish people to self-purification and moral perfection in order to save the mankind.
Keywords: B Philosophy; Psychology; Religion; B Philosophy